THE ROLE OF DIGITAL MEDIA IN MARKETING TRANSFORMATION: A COMPARATIVE STUDY OF VARIOUS INDUSTRIES - Rudianto; Ignatius Septo Pramesworo; Jeffry H. Sinaulan (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research explores the role of digital media in marketing transformation across various industries, focusing on how these technologies are transforming traditional marketing strategies into more dynamic and focused ones. Analyses were conducted on a comparative basis to understand the different adoption and implementation rates of digital media in sectors such as retail, entertainment, agriculture and manufacturing. Findings show that industries that are more directly connected to consumers, such as retail and entertainment, have been quicker to adopt digital solutions, while industries with more complex supply chains face greater challenges. The study confirms the importance of digital media in providing greater marketing flexibility and efficiency, and encourages companies to adapt and innovate to maintain competitiveness in the evolving digital economy.